2019
DOI: 10.1002/ange.201903759
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Phenol Coupling by Laccases in the Biosynthesis of Fungal Dimeric Naphthopyrones

Abstract: Biaryl compounds are ubiquitous metabolites that are often formed by dimerization through oxidative phenol coupling.Hindered rotation around the biaryl bond can cause axial chirality.I nn ature,d imerizations are catalyzed by oxidative enzymes such as laccases.T his class of enzymes is knownf or non-specific oxidase reactions while inherent enantioselectivity is hitherto unknown. Here,w ed escribe four related fungal laccases that catalyze g-naphthopyrone dimerization in ar egio-and atropselective manner.I nvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…The A. aculeatus bfoB strain yielded nigerone (2a) and bifonsecin B (2b); the A. aculeatus aunB strain yielded aurasperone A (3a) and aurasperone B (3b). For the other monomeric substances, fonsecin (5) and flavasperone (6), no formation of dimers was detected.…”
mentioning
confidence: 91%
“…The A. aculeatus bfoB strain yielded nigerone (2a) and bifonsecin B (2b); the A. aculeatus aunB strain yielded aurasperone A (3a) and aurasperone B (3b). For the other monomeric substances, fonsecin (5) and flavasperone (6), no formation of dimers was detected.…”
mentioning
confidence: 91%
“…The bis-naphthopyrone-type pigments are widely produced by different fungi that can protect filamentous fungi from fungivores [ 62 ] or abiotic stress factors like UV radiation and high temperatures [ 63 , 64 ]. Genome survey indicated that both C. militaris and C. cicadae contain a conserved PKS BGC like that of rice false smut Ustilaginoidea virens ( Figure 3 D), which is responsible for the production of ustilaginoidins [ 65 ]. Different analogs of ustilaginoidins have varied level of antibacterial, cytotoxic, and phytotoxic activities [ 66 ].…”
Section: Unknown Mycotoxins May Be Produced By Cordycepsmentioning
confidence: 99%
“…Nature has evolved catalysts for oxidative dimerization of phenolic compounds to generate biaryl natural products. 53,54 Whereas a growing number of these catalysts have been identified in biosynthetic pathways of biaryl natural products (Supplemental Table S2), [55][56][57][58][59][60][61][62][63][64][65][66][67][68] a much more vast pool of related sequences remains underexplored with untapped potential to catalyze a diverse array of oxidative coupling reactions (see sequence similarity network, SSN, in Figure 1d). Both laccases and cytochrome P450 monooxygenases (P450s) are known to carry out this transformation.…”
mentioning
confidence: 99%
“…Both laccases and cytochrome P450 monooxygenases (P450s) are known to carry out this transformation. 9 Although laccases have been employed in biocatalysis, these enzymes have only been shown to exert control over the selectivity of the C-C bond-forming event following the initial oxidation in a limited number of examples, 68,69 as laccases more commonly afford complex product mixtures. 70,71 In contrast, P450s associated with secondary metabolite biosynthesis often exhibit excellent control over the site-and atroposelectivity in oxidative coupling reactions.…”
mentioning
confidence: 99%